The Influence of Leadership and Organizational Culture on Employee Performance at PT Nexus Kargo Indonesia - Adhani Cahyadi; Frida Aprillia (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
The employee performance can be influenced by the leadership style and organizational culture in the company. The purpose of this research is to determine and analyze the influence of leadership on employee performance, to determine and analyze the influence of organizational culture on employee performance and to analyze the influence of leadership and organizational culture on employee performance at PT. Nexus Kargo Indonesia. The method used in this research is a quantitative method. The data collection technique in this research uses questionnaires. The data analysis technique in this research uses the Classical Assumption Test, Multiple Regression, t-test and F Test, and Determination Coefficient. Data processing in this research uses the SPSS software program. From the results of this research, leadership partially has a significant positive influence on employee performance because the significance value is 0.00 < 0.05. Partially, organizational culture has a significant positive influence on employee performance because the significance value is 0.00<0.05. From the results of the f test, the significance value is 0.000, which is smaller than 0.05, which means there is a significant positive influence. Simultaneously, leadership and organizational culture have a significant positive influence on employee performance at PT Nexus Kargo Indonesia.